Analisis Kompetensi Guru Dalam Penyusunan Laporan Arus Kas - Salma Taqwa; Erinos Erinos; Halkadri Fitra (Universitas Negeri Padang, 2021)
This study looks at the differences in teacher competence before the training in preparing cash flow reports compared to after the training. This training aims to improve the competence of vocational school teachers in accounting, which expects to increase student competence in the UKK Test. UKK test for SMK students, one of the materials, is the completion of the accounting cycle, including preparing cash flow statements. To know the results of the training, SMK teachers as participants did the pretest and posttest. Then, the T-test was carried out and resulted that Ho is rejected, and Ha is accepted. Thus, it can be concluded that this training increases the competence of teachers in preparing cash flow reportsKeywords : competence, training, cash flow statement